Against imperialist penetration and repression : university autonomy (International Union of Students, 1971)
High contrast photos of military police arresting person and of a demonstration; colours of poster refer to the Venezuelan flag Poster advertising day of solidarity with Venezuela, 21 November, 1971 PO-0404